The forecasting performance of implied volatility : Does the level of volatility matter? - Eirola, Juuso (My University, 2021)
This thesis examines the forecasting accuracy of implied volatility and investigates whether the expected volatility of implied volatility or the market volatility level affects the forecasting performance. Therefore, the OLS and quantile regressions are used to test the relationship between future realised volatility and the VIX index on various levels of market volatility. In addition, the impact of the VVIX index on the absolute percentage deviation between S&P 500 realised volatility and one-month lagged VIX is examined. The realised volatility is estimated using the range-based volatility estimator. Consistent with prior literature, the results show that implied volatility is a reasonable but biased forecast of future volatility over a one-month forecasting horizon. The conclusion remains the same regardless of whether overlapping data, non-overlapping data or log-transformed variables are used. The forecasting accuracy seems to increase during periods of high market volatility. However, the results for the quantile regression indicate that the forecasting accuracy does not significantly vary within the level of realised volatility. Moreover, the implied volatility of the VIX index seems to be negatively associated with the forecasting performance of VIX.

Tämä tutkielma tarkastelee implisiittisen volatiliteetin kykyä ennustaa tulevaisuuden realisoitu-nutta volatiliteettia. Tavoitteena on selvittää, vaikuttaako implisiittisen volatiliteetin odotettu volatiliteetti tai markkinavolatiliteetin taso ennustetarkkuuteen. Pienimmän neliösumman me-netelmää ja kvantaaliregressiota käytetään tulevaisuuden realisoituneen volatiliteetin ja VIX-indeksin välisen yhteyden analysointiin volatiliteetin eri tasoilla. Lisäksi tarkastellaan, vaikut-taako VVIX-indeksi S&P 500 -indeksin ja yhden kuukauden takaisen VIX-indeksin absoluuttiseen prosentuaalisen hajontaan. Realisoitunut volatiliteetti estimoidaan käyttäen päivittäisten avaus- ja päätösarvojen lisäksi päivän korkeinta sekä matalinta arvoa. Aiempien tutkimusten mukaisesti tutkimustulokset osoittavat, että implisiittinen volatiliteetti kykenee ennustamaan tulevaa 30 päivän volatiliteettia, mutta se ei ole harhaton estimaattori. Johtopäätökset pysyvät muuttumattomina riippumatta siitä, käytetäänkö päällekkäisiä havain¬toja tai muuttujien logaritmisia muunnoksia. Ennustetarkkuus näyttää kasvavan korkean mark-kinavolatiliteetin aikoina. Toisaalta kvantaaliregression tulosten mukaan ennustetarkkuudessa ei ole tilastollisesti merkittäviä eroja realisoituneen volatiliteetin eri tasojen välillä. VIX-indeksioptioista johdetulla implisiittisellä volatiliteetilla näyttää puolestaan olevan negatiivinen vaikutus VIX-indeksin ennustekykyyn.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance